ABOUT A «DIGITAL TWIN» OF A FOOD PRODUCT - Marina A. Nikitina; Irina M. Chernukha; Andrey B. Lisitsyn (Теория и практика переработки мяса)
The paper presents definitions of digital twins. The authors examine a hypothesis that a digital twin of a food product is a mathematical (simulation) model that includes the whole variety of factors influencing quality and safety. An approach to the mathematical setting of the structural optimization task at different stages of description of the technology for a food product digital twin is analyzed. The first stage, which has several levels, is connected with correspondence of the nutritional and biological values to the medico-biological requirements. The second stage is linked with predetermination of structural forms, the third with perception of sensory characteristics (color, odor and so on). The universal method for assessment of quality and efficiency of a food product digital twin using the generalized function (integral index) is described. Different individual responses can be components of the additive integral index: physico-chemical, functional-technological and organoleptic.